A guide to architecture for the public health workforce. (January 2020) - Marsh, R.; Pilkington, P.; Rice, L.
Abstract: Background: Public health and environmental challenges facing the world in the 21st century, including the ageing population, increasing urbanisation, rise of non-communicable diseases and climate instability, require an interdisciplinary response. A significant proportion of the population's time is spent indoors, be it at home, school, work or in leisure time; the work of an architect can cover all of these sectors, but their role in health and well-being remains an under explored area. Objective: This article examines the architecture profession's potential to contribute to improved health and well-being of the population through healthier buildings and places. Methodology: This short communication adopts a descriptive approach. First, it maps the remit, skills and influence of the architecture profession and applies this to a well-accepted public health model, the prevention pyramid. Second, it uses themes identified by the Royal Society for Public Health to discuss ways to improve engagement with the architecture profession as part of the wider public health workforce. Results: This article finds that the remit, skills and potential influence of architects places them in a key position to improve the health and well-being of the population. Despite this, there has been relatively little engagement between public health and this profession. Much more attention to date has been on integrating the planning sector with public health. Conclusion: Opportunities for improved engagement exist through partnership working, incorporating health into both undergraduate and postgraduate education and continuing professional development training, building the evidence base and developing architecture and health-related policy and legislation. Highlights: The architecture profession can contribute to primary, secondary and tertiary prevention. There has been little engagement between public health and the architecture profession. Opportunities are partnership working, addressing training needs and building the evidence base.